Quality of Life in Patients with Acne: A Questionnaire Study - Parajuli, Niraj; Kayastha, Bhasker Mohan Meher (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Introduction: Acne vulgaris is a self-limited disorder of the pilosebaceous unit. It is primarily seen in adolescent age group. Acne can present with pleomorphic lesions consisting of comedones, papules, pustules and nodules. Both inflammatory and non-inflammatory acne can produce scarring. It has been found that acne significantly affects self-image and quality of life. Effective treatment results in improvement of quality of life. Objective: The objective of this study was to find the impairment of quality of life in patients with acne. Materials and Methods: A total of 140 randomly selected patients coming to Dermatology OPD of Bir Hospital with complaints of acne were enrolled. A standard Dermatology Life Quality Index (DLQI) and Cardiff Acne Disability Index (CADI) questionnaires were used. Results: The average score of DLQI in my study was 9.5±5.6 with a minimum score of 0 and maximum score of 25. Similarly, the mean CADI score was 5.9±2.88 with minimum score of 0 and maximum score of 12. This study found acne to be more common in females as compared to males. Most common age group for acne was 16-20 years. Almost half of the patients (46%) complained of flare-ups during summer season. Similarly, majority (60%) of patients could relate to some aggravating factors. Most common aggravating factors were topical medications, fatty foods and stress. Conclusion: Acne is a common skin condition among the adolescents. This study conducted in Dermatology and Venereology Department of Bir Hospital showed that there is invariably some impairment in quality of life in acne patient.